Preparation of a Novel Ni-In Alloy Electrode and its Electrocatalytic Activity - Kuang, Dai-Zhi; Li, Jun-Hua; Feng, Yong-Lan; Zhang, Fu-Xing; Wang, Jian-Qiu (Asian Journal of Chemistry, 2010)
Nickel electrode, indium electrode and two kinds of Ni-In alloy electrodes (A-type and B-type) were prepared by electrodeposition method and their voltammetric behaviours were investigated in a 0.2 mol/L NaOH solution. The electrocatalytic activities of glucose on these electrode surfaces were also examined. The results of electrochemical experiments indicated that the Ni electrode and Ni-In alloy electrodes had catalysis effect on glucose oxidation in an alkaline solution. The A-type Ni-In alloy electrode, prepared in an electrolyte at a 5:1 Ni2+/In3+ mole ratio, had the best electrocatalytic activity. There was a liner relationship between glucose oxidation peak current and its concentration in the range of 1-10 mmol/L. The A-type Ni-In alloy electrode in alkaline solution was steady and it preferably resisted surface poisoning. This alloy electrode can be used as a high catalytic activity electrode of glucose sensor and glucose fuel cell.